Solution structure of ribosomal protein L40E, a unique C4 zinc finger protein encoded by archaeon Sulfolobus solfataricus - Wu, Bin (Cold Spring Harbor Laboratory Press, 2008)

(untitled)
The ribosomal protein L40E from archaeon Sulfolobus solfataricus is a component of the 50S ribosomal subunit. L40E is a 56-residue, highly basic protein that contains a C4 zinc finger motif, CRKC_X(10)_CRRC. Homologs are found in both archaea and eukaryotes but are not present in bacteria. Eukaryotic genomes encode L40E as a ubiquitin-fusion protein. L40E was absent from the crystal structure of euryarchaeota 50S ribosomal subunit. Here we report the three-dimensional solution structure of L40E by NMR spectroscopy. The structure of L40E is a three-stranded β-sheet with a simple β2β1β3 topology. There are two unique characteristics revealed by the structure. First, a large and ordered β2–β3 loop twists to pack across the one side of the protein. L40E contains a buried polar cluster comprising Lys19, Lys20, Cys22, Asn29, and Cys36. Second, the surface of L40E is almost entirely positively charged. Ten conserved basic residues are positioned on the two sides of the surface. It is likely that binding of zinc is essential in stabilizing the tertiary structure of L40E to act as a scaffold to create a broad positively charged surface for RNA and/or protein recognition.